1999
DOI: 10.1038/sj.onc.1202294
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of NF1 type I and type II isoforms in sporadic borderline and invasive epithelial ovarian tumors

Abstract: The NF1 gene, a putative tumor suppressor gene, contains a GAP related domain (GRD) which accelerates hydrolysis of ras-bound GTP to GDP, thereby converting the ras oncogene from its active to inactive form. Two forms of the NF1 GRD transcript (Type I and Type II) are di erentially expressed in neuroectodermal tumor tissue relative to di erentiated neural cells, and in gastric cancer cell lines relative to normal stomach mucosa. We measured relative expression of NF1 Type II and Type I isoforms in cultured nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
1
6
0
1
Order By: Relevance
“…Our data are consistent with a role for keratinocytes, and perhaps injury, in the abnormal skin pigmentation characteristic of NF1 patients. In addition, chromosome 17 loss in the region of human NF1 is frequently observed in carcinomas, as is downregulation of neurofibromin expression (Hermonen et al, 1995;Wertheim et al, 1996;Aaltonen et al, 1999;Dunn et al, 1999;Iyengar et al, 1999). Our experiments using a mouse model support the idea that NF1 could play a part in human epithelial carcinogenesis.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Our data are consistent with a role for keratinocytes, and perhaps injury, in the abnormal skin pigmentation characteristic of NF1 patients. In addition, chromosome 17 loss in the region of human NF1 is frequently observed in carcinomas, as is downregulation of neurofibromin expression (Hermonen et al, 1995;Wertheim et al, 1996;Aaltonen et al, 1999;Dunn et al, 1999;Iyengar et al, 1999). Our experiments using a mouse model support the idea that NF1 could play a part in human epithelial carcinogenesis.…”
Section: Discussionsupporting
confidence: 76%
“…NF1 dysfunction may also occur in sporadic epithelial tumors. Regions of loss of heterozygosity including NF1 have been reported in breast, ovarian, and esophageal cancer (Wertheim et al, 1996;Dunn et al, 1999), NF1 message is downregulated in epithelial ovarian cancer (Iyengar et al, 1999) and neurofibromin expression is downregulated in urinary bladder transitional cell carcinogenesis (Aaltonen et al, 1999). This recent evidence supports a function for NF1 in epithelial cell tumorigenesis.…”
mentioning
confidence: 84%
“…27 In 1991, Nishi et al found that isoform type I was the dominantly expressed isoform in fetal brain and undifferentiated neuroectodermal tumours while isoform type II was present in well differentiated tumours. 14 Iyengar and colleagues 16 analysed expression of these two isoforms in ovarian carcinoma and detected a significant decrease in isoform type II expression and an increase in isoform type I expression in ovarian carcinoma cell lines and tumour tissue with respect to expression of these two isoforms in normal ovarian epithelial cells. Dominant expression of isoform type II was detected in normal gastric mucous while both isoforms were equally expressed in gastric cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…14 Iyengar et al analysed expression of these two isoforms in ovarian carcinoma and detected a significant decrease in isoform type II expression and an increase in isoform type I expression in ovarian carcinoma cell lines and tumour tissue compared with expression of these two isoforms in normal ovarian epithelial cells. 16 As neurofibromin acts as a negative regulator of Ras, which is involved in the tumorigenesis of many cancers, including colon cancer, the aim of our study was to investigate the role of the NF1 gene in the development and progression of sporadic colon cancer. Here we analysed loss of heterozygosity (LOH) at the NF1 gene locus, NF1 mRNA expression, NF1 mRNA isoform type I and II expression, and neurofibromin expression in sporadic colon cancer.…”
mentioning
confidence: 99%
“…Several studies have shown that alteration in the type II versus type I ratio can be related with the development of certain malignancies. For instance, in colon and ovarian cancers, the predominant transcript is type I 9 10. At present, there are a few reports on NF1 expression and breast cancer, mainly in patients affected by NF1 disease 11 12…”
Section: Introductionmentioning
confidence: 99%